Increase OEE at Manual Assembly Lines by Data Mining - Dobra, Peter; Jósvai, János (Acta Technica Jaurinensis, 2020)
The industrial companies often use Key Performance Indicators (KPI) to follow up and evaluate their process and success. One of the KPIs is the Overall Equipment Effectiveness (OEE) which represents the efficiency of the manufacturing area. The high OEE value means good performance of the machines or lines. This paper presents a method in order to increase OEE at the manual assembly lines by data mining. Firstly, a literature review demonstrates scientific relevance. Secondly, a method is introduced for improving the efficiency with the help of the recognised patterns. Using Manufacturing Execution System (MES) data the OEE percentage was increased by 8% in 3 months without any financial investment.